ADOPTION AND UTILIZATION OF CLIMATE SMART AGRICULTURAL PRACTICES BY CASSAVA FARMING HOUSEHOLDS IN IDO LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
The study examined the adoption and utilization of Climate Smart Agricultural Practices (CSAP) by cassava farming households in Ido Local Government Area, Oyo State, Nigeria. A two-stage sampling procedure was used to purposively select one hundred and twenty (120) registered farmers engaged in cassava crop production for questionnaire administration. Data obtained were analysed using descriptive and inferential statistics. The study revealed that cassava farming activities in the study area is at a small scale level owing to the size of farmland cultivated by majority (70.0%) of the respondents’. It was also observed that majority (76.7%) of the respondents’ in the study area generally have adequate knowledge of climate smart agricultural practices though their mean adoption score (4.38) is critically low. This may be linked to the respondents’ low level of literacy and the barriers affecting the adoption and utilization of climate agricultural practices. The study inferred that there is probably need for more awareness about the potentials of these practices in increasing agricultural productivity in the study area. Variables such as education, farming experience, size of farmland, access to credit and access to extension services were all significant at 0.05 level of significance. It is therefore recommended that extension officers, relevant agencies/associations should develop suitable policies that will encourage farmers’ especially rural farmers’ to adopt and utilize Climate Smart Agricultural Practices (CSAP). This will, in the mid and long term, help in boosting farmers’ income and enhancing sustainable food security
Keywords: Cassava production, climate change, adoption, climate smart agricultural practices